Medicine manipulation : an alternative to mitigate therapeutic gaps in the Brazilian Unified Health System? - Okamoto, Gabriel Gonçalves (2022)
Despite the various initiatives carried out in Brazil and in the world, the challenge of offering essential medicines in adequate presentations remains, especially to the public affected by diseases considered neglected and the pediatric population, for whom the therapeutic options remain limited. The main objective of this study was to evaluate the production of manipulated medicines as a strategy to mitigate therapeutic and access gaps to essential medicines within the Brazilian public health system, called the Unified Health System (SUS). The evaluation, carried out between 2020 and 2021, identified, among the medicines considered essential to the Brazilian health context, those unavailable, for which strategies were evaluated to mitigate the identified unavailability, which is conventionally called therapeutic gaps. For 57% (n = 235) of pharmaceutical presentations identified as therapeutic gaps in SUS, manipulation was identified as the best strategy to promote access. Of these presentations, 30% (n = 70) were identified as priorities in the context of patient care and were mainly related to the demands of the pediatric public and those affected by poverty-related diseases. Concerning poverty-related diseases, the absence of evidence on the development of a standard formula for drugs with indication for such diseases was demonstrated. The need for an annual investment of approximately US$74.75 per capita was estimated to offer treatments in adequate presentations to SUS users, which should reflect in the improvement of the quality of life of about 26 thousand people. It was observed that this investment amount corresponds to only 3% of the budget for the purchase of medicines financed exclusively by the Ministry of Health thorugh the Strategic Component of Pharmaceutical Assistance (CESAF) approved for 2021.